Thermal ecology of Zonocerus variegatus and its effect on biocontrol using pathogens - Blanford, S.; Thomas, M.B.; Langewald, J. (Wiley, 2000)
1 Thermal behaviour of the variegated grasshopper, Zonocerus variegatus, was investigated in the humid tropical zone of southern Benin, west Africa, in the dry seasons of 1996 and 1998. In 1998, investigations included studies of a population of grasshoppers sprayed with an oil‐based formulation of the entomopathogenic fungus Metarhizium anisopliae var acridum. 2 Body temperature measurements and observations of thermal behaviour both in the field and on thermal gradients in the laboratory, suggest that Z. variegatus was not an active behavioural thermoregulator. Although it did show shade‐seeking behaviour at high temperatures, no overt behavioural postures or microhabitat selection associated with heat gain and elevation of body temperatures was observed. Moreover, no alterations to thermal behaviour were found in response to infection by Metarhizium. 3 Body temperatures exhibited by Z. variegatus in the field will lengthen disease incubation of M. anisopliae var acridum compared with laboratory maintained, constant temperature conditions and may have a significant impact on pathogens with a lower thermal tolerance. 4 Habitat structure appeared to be an important factor determining the extent of body temperature elevation. The effect of habitat differences on infection and growth of M. anisopliae var acridum and other entomopathogenic fungi is discussed.